2015
DOI: 10.1007/s40615-015-0185-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Efficacy and Control for Neighborhood Change: the Cross-Cutting Role of Collective Efficacy

Abstract: Background The premise of community advocacy is to empower residents by increasing their capacity to address and change neighborhood and structural factors that contribute to adverse health outcomes. An underlying assumption is that community residents will advocate for public policy and other changes. However, limited empirical evidence exists on community residents' perceived ability to advocate for neighborhood change. In this study, we characterized perceived neighborhood control and efficacy for neighborh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Studies suggest associations between collective efficacy and greater life satisfaction (Driscoll et al, 2015), better self-reported health (Browning & Cagney, 2002), increased confidence in the ability to make neighborhood improvements (Rice et al, 2016), and protection against the effects of racial discrimination (Driscoll et al, 2015).…”
Section: Social and Neighborhood-level Coping And Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest associations between collective efficacy and greater life satisfaction (Driscoll et al, 2015), better self-reported health (Browning & Cagney, 2002), increased confidence in the ability to make neighborhood improvements (Rice et al, 2016), and protection against the effects of racial discrimination (Driscoll et al, 2015).…”
Section: Social and Neighborhood-level Coping And Healingmentioning
confidence: 99%
“…Also important are programs or initiatives that build social cohesion and collective efficacy (Driscoll et al, 2015;Johns et al, 2012), such as grassroots neighborhood associations and organizations that provide opportunities for residents to come together, organize, and develop their neighborhoods into vibrant, safe spaces (Rice et al, 2016).…”
Section: F I G U R E 1 a Mutual Process Of Healing Self And Healing The Communitymentioning
confidence: 99%
“…In addition, high quality outdoor spaces and good community administration restraint residents toward community participation. In other words, perceived neighborhood problems that included planning factors of the physical environment have been shown to motivate residents into collective action [10,62,63]. In sum, the first canonical function suggests that outdoor space quality and community layout promote place relationships of the residents.…”
Section: The Canonical Functions Betwwen Planning Factors and Place Rmentioning
confidence: 99%
“…In order to provide debriefing and dissemination of the results of a research investigation to participants and targeted audiences, technology can also assist through the distribution of a podcast or youTube video of the investigator reporting the findings. Studies have assessed the preference of research participants in receiving research results and have demonstrated more likelihood of future participation when there is ongoing communication about the research product or conclusions (Hughes Halbert et al, 2014; Rice et al, 2016). Grand scale dissemination can also help with increasing awareness of new potential procedures and/or services.…”
Section: Introductionmentioning
confidence: 99%